2010
DOI: 10.1111/j.1442-9071.2010.02306.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported vision and health of indigenous Australians

Abstract: The National Indigenous Eye Health Survey provided information to guide future planning of eye health prevention strategies for indigenous Australians. Findings indicate the importance of correcting refractive error to improve quality of life. Prevention messages should be renewed in appropriate sociocultural formats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The NIEHS found that 54% of those with self-reported DR had no clinical evidence of DR on examination, and of those found to have DR, 60% did not report a previous history of this. 36 The DRUID found similar results for DM diagnosis in an urban setting, with 28% of participants with a diagnosis of DM newly diagnosed in the study. 19 Variations have also been identified in non-Indigenous studies, with rates of undiagnosed DM in non-Indigenous Australians living in rural areas similar to those seen in Indigenous studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The NIEHS found that 54% of those with self-reported DR had no clinical evidence of DR on examination, and of those found to have DR, 60% did not report a previous history of this. 36 The DRUID found similar results for DM diagnosis in an urban setting, with 28% of participants with a diagnosis of DM newly diagnosed in the study. 19 Variations have also been identified in non-Indigenous studies, with rates of undiagnosed DM in non-Indigenous Australians living in rural areas similar to those seen in Indigenous studies.…”
Section: Discussionsupporting
confidence: 65%
“…Significant inconsistencies have been reported when comparing self‐reported rates and actual rates of health problems in Indigenous communities. The NIEHS found that 54% of those with self‐reported DR had no clinical evidence of DR on examination, and of those found to have DR, 60% did not report a previous history of this . The DRUID found similar results for DM diagnosis in an urban setting, with 28% of participants with a diagnosis of DM newly diagnosed in the study .…”
Section: Discussionmentioning
confidence: 65%
“…In addition to this, we found that living in Inner Regional, Remote and Very Remote Coastal areas also decreased the odds of reporting a problem. These results could be reflective of the lower rates of refractive error previously reported in remote areas for Indigenous adults, 9 but further studies maybe needed to help tease out and explain these findings.…”
Section: Discussionmentioning
confidence: 77%
“…For adults, a questionnaire was used to collect data on demographics (gender, age and language spoken at home), general health, history of eye health, vision‐related QoL and health service utilization 9 …”
Section: Methodsmentioning
confidence: 99%
“…Although the patient's self-reported AMD history is unreliable, 38,51 an inquiry of patient history that includes known AMD risk factors will help to identify high-risk patients. Adults $ 55 years and having two or more of the AMD risk factors should be followed-up annually.…”
Section: Patient Historymentioning
confidence: 99%